A Pre-Test via Partial Least Square Structural Equation Modeling with the Influence of Organisational Structures and Organisational Internal Factors on Construction Risk Management Among Malaysian Construction Industries - Omer, Manal Suliman; Adeleke, A. Q.; Lee, Chia Kuang (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
An increased demand has been placed on construction projects to be more accountable to their clients with measure to the company services and outputs. This demand is because of innumerable antecedent factors repelling risk management in construction projects. However, finishing the projects is not only the concern of the industries but also managing the risks involved with the projects. This paper investigated the effects of organizational structure and internal factors on the risk management among G7 contractors in Malaysia. The purpose of this study is threefold: (i) to propose an inclusive research model which comprises of the antecedent factors proposed in the model to improve effective risk management in Malaysia construction industries (ii) to serve as a validation process for the developed instrument of the on-going research with the identified constructs of the study (iii) to show the preliminary analysis and the results. A pilot study was conducted, data was collected and a total of thirty (30) respondents’ responses were analysed using a questionnaire of eighty-one items. This was conducted to access and validate how reliable the analytical tools (i.e PLS-SEM model) used in the survey were. The results obtained indicated that the reliability of the measurement model and the ensuing data for pilot study suggested a veritable evidence of their validity.